Maximizing the encapsulation efficiency and the bioavailability of controlled-release cetirizine microspheres using Draper–Lin small composite design - El-Say KM (Dove Medical Press, 2016)
Khalid Mohamed El-Say1,2 1Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, King Abdulaziz University, Jeddah, Kingdom of Saudi Arabia; 2Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Al-Azhar University, Cairo, Egypt Abstract: This study was aimed at developing a controlled-release cetirizine hydrochloride (CTZ)-loaded polymethacrylate microsphere by optimization technique using software-based response surface methodology. The emulsion solvent evaporation method was utilized in the preparation of microspheres. Four process variables were selected, namely, Eudragit RLPO loading percentage in total polymer, the emulsifier hydrophilic lipophilic balance (HLB), the antitacking percentage, and the dispersed phase volume. The desired responses were particle size, angle of repose, production yield, encapsulation efficiency, loading capacity, initial drug release, and the time for 85% of drug release from the microspheres. Optimization was carried out by fitting the experimental data to the software program (Statgraphics Centurion XV). Moreover, 18 batches were subjected to various characterization tests required for the production of dosage form. The pharmacokinetic parameters were evaluated after the oral administration of 10 mg CTZ in both optimized formulation and commercial product on healthy human volunteers using a double-blind, randomized, cross-over design. The optimized formulation showed satisfactory yield (84.43%) and drug encapsulation efficiency (87.1%). Microspheres were of spherical shape, smooth surface, and good flowability with an average size of 142.3 µm. The developed optimized batch of microspheres ensured 28.87% initial release after 2 hours, and the release of CTZ extended for >12 hours. In addition, the relative bioavailability of the optimized formulation was 165.5% with respect to the marketed CTZ tablets indicating a significant enhancement of CTZ bioavailability. Thus, there is an expectation to decrease the administered dose and the frequency of administration, and subsequently minimize the adverse effects that are faced by the patient during the treatment. Keywords: emulsion solvent evaporation, Eudragit, experimental design, in vivo, optimization, response surface